1999
DOI: 10.1128/jvi.73.10.8201-8215.1999
|View full text |Cite
|
Sign up to set email alerts
|

Role of Immune Responses against the Envelope and the Core Antigens of Simian Immunodeficiency Virus SIVmne in Protection against Homologous Cloned and Uncloned Virus Challenge in Macaques

Abstract: We previously showed that envelope (gp160)-based vaccines, used in a live recombinant virus priming and subunit protein boosting regimen, protected macaques against intravenous and intrarectal challenges with the homologous simian immunodeficiency virus SIVmne clone E11S. However, the breadth of protection appears to be limited, since the vaccines were only partially effective against intravenous challenge by the uncloned SIVmne. To examine factors that could affect the breadth and the efficacy of this immuniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(13 citation statements)
references
References 96 publications
2
11
0
Order By: Relevance
“…Our observation that CL8 vaccines protected against homologous CL8 challenge is consistent with our previous findings [13,[31][32][33], although different challenge viruses and animal species were used (molecular clone and pig-tailed macaques in the current study vs. biological clone E11S and cynomolgus macaques in previous ones). Also in line with our previous observation [31,32] is the finding that CL8 vaccines failed to protect against a highly virulent virus 170. However, protective efficacy of the CL8 vaccines was not restricted to the minimally pathogenic homologous virus, as protection and substantial reduction of viral load was achieved in CL8-immunized macaques challenged by the 170/8 chimera, infection by which resulted in high and persistent viremia accompanied by progressive and irreversible CD4 + T cells loss.…”
Section: Vaccines From Temporal Isolates Of Sivmnesupporting
confidence: 91%
“…Our observation that CL8 vaccines protected against homologous CL8 challenge is consistent with our previous findings [13,[31][32][33], although different challenge viruses and animal species were used (molecular clone and pig-tailed macaques in the current study vs. biological clone E11S and cynomolgus macaques in previous ones). Also in line with our previous observation [31,32] is the finding that CL8 vaccines failed to protect against a highly virulent virus 170. However, protective efficacy of the CL8 vaccines was not restricted to the minimally pathogenic homologous virus, as protection and substantial reduction of viral load was achieved in CL8-immunized macaques challenged by the 170/8 chimera, infection by which resulted in high and persistent viremia accompanied by progressive and irreversible CD4 + T cells loss.…”
Section: Vaccines From Temporal Isolates Of Sivmnesupporting
confidence: 91%
“…For the most part, a direct comparison to most of these studies is not possible as a result of numerous dierences in experimental protocols. Dierences include animal age, mode of DNA inoculation, use of plasmid vectors or vaccinia virus for priming inoculation, choice of boosting components, challenge routes, and virus strains [26,32,43,46]. However, one study that closely approximated ours in both design and immunizing reagents was completed recently in juvenile macaques [51].…”
Section: Discussionmentioning
confidence: 99%
“…A challenge model using SHIV infection of macaques now allows for the testing of vaccines that are aimed at inducing a response against HIV-1 envelope glycoproteins. In such a system, however, testing of HIV-1 gag or pol components is not possible, and experiments using SIV have suggested that immune responses against these viral proteins are important in achieving protection [25]. These developments again underline the need for an animal model that uses HIV-1 rather than SIV or SHIV.…”
Section: Introductionmentioning
confidence: 99%